A CMOS image sensor with a double-junction active pixel. - Findlater, K.M (IEEE Transactions on electron devices)
A CMOS image sensor that employs a vertically integrated double-junction photodiode structure is presented. This allows color imaging with only two filters. The sensor uses a 184*154 (near-QCIF) 6-transistor pixel array at a 9.6-μm pitch implemented in 0.35-μm technology. Results of the device characterization are presented. The imaging performance of an integrated two-filter color sensor is also projected, using measurements and software processing of subsampled images from the monochrome sensor with two color filters.